Global patterns of nitrate storage in the vadose zone. Issue 1 (December 2017) - Ascott, M.; Gooddy, D.; Wang, L.; Stuart, M.; Lewis, M.; Ward, R.; Binley, A.
Abstract Global-scale nitrogen budgets developed to quantify anthropogenic impacts on the nitrogen cycle do not explicitly consider nitrate stored in the vadose zone. Here we show that the vadose zone is an important store of nitrate that should be considered in future budgets for effective policymaking. Using estimates of groundwater depth and nitrate leaching for 1900–2000, we quantify the peak global storage of nitrate in the vadose zone as 605–1814 Teragrams (Tg). Estimates of nitrate storage are validated using basin-scale and national-scale estimates and observed groundwater nitrate data. Nitrate storage per unit area is greatest in North America, China and Europe where there are thick vadose zones and extensive historical agriculture. In these areas, long travel times in the vadose zone may delay the impact of changes in agricultural practices on groundwater quality. We argue that in these areas use of conventional nitrogen budget approaches is inappropriate. Current global-scale nitrogen (N) budgets quantifying anthropogenic impacts on the N cycle do not explicitly consider nitrate storage in the vadose zone. Here, using estimates of depth to groundwater and nitrate leaching between 1900–2000, the authors show that the vadose zone is an important store of nitrate.